Modestobacter altitudinis sp. nov., a novel actinobacterium isolated from Atacama Desert soil - Golińska, Patrycja; Świecimska, Magdalena; Montero-Calasanz, Maria del Carmen; Yaramis, Adnan; Igual, Jose M.; Bull, Alan T.; Goodfellow, Michael (International journal of systematic and evolutionary microbiology, 2020)
Three presumptive Modestobacter strains isolated from a high altitude Atacama Desert soil were the subject of a polyphasic study. The isolates, strains 1G4 T , 1G51 and 1G52, were found to have chemotaxonomic and morphological properties that were consistent with their assignment to the genus Modestobacter . They formed a well supported clade in Modestobacter 16S rRNA gene trees and were most closely related to the type strain of ‘Modestobacter excelsi’ (99.8–99.9% similarity). They were also closely related to the type strains of Modestobacter caceresii (99.6 % similarity), Modestobacter italicus (99.7–99.9% similarity), Modestobacter lacusdianchii (98.4–99.2% similarity), Modestobacter marinus (99.4–99.5% similarity) and Modestobacter roseus (99.3–99.5% similarity), but were distinguished from their closest relatives by a combination of phenotypic features. Average nucleotide identity and digital DNA:DNA hybridization similarities drawn from comparisons of draft genome sequences of isolate 1G4 T and its closest phylogenetic neighbours mentioned above, were well below the threshold used to assign closely related strains to the same species. The close relationship between isolate 1G4 T and the type strain of M. excelsi was showed in a phylogenomic tree containing representative strains of family Geodermatophilaceae . The draft genome sequence of isolate 1G4 T (size 5.18 Kb) was shown to be rich in stress related genes providing further evidence that the abundance of Modestobacter propagules in Atacama Desert habitats reflects their adaptation to the harsh environmental conditions prevalent in this biome. In light of all of these data it is proposed that the isolates be assigned to a novel species in the genus Modestobacter . The name proposed for this taxon is Modestobacter altitudinis sp. nov., with isolate 1G4 T (=DSM 107534 T =PCM 3003 T ) as the type strain.